Swelling of Zein Matrix Tablets Benchmarked against HPMC and Ethylcellulose: Challenging the Matrix Performance by the Addition of Co-Excipients - Berardi, Alberto (Pharmaceutics, 2019)
Zein is an insoluble, yet swellable, biopolymer that has been extensively studied for its applications in drug delivery. Here, we screened the effect of co-excipients on the swelling and drug release of zein tablets. All throughout the study the behavior of zein was benchmarked against that of hydroxypropyl methylcellulose (HPMC) and ethylcellulose (EC). Tablets containing either zein, HPMC, or EC alone or in combination with co-excipients, namely lactose, dicalcium phosphate (DCP), microcrystalline cellulose (MCC), polyvinylpyrrolidone (PVP), or sodium lauryl sulfate (SLS) were prepared by direct compression. Matrix swelling was studied by taking continuous pictures of the tablets over 20 h, using a USB microscope connected to a PC. The overall size change and the axial and radial expansion of the tablets were automatically extrapolated from the pictures by image analysis. Moreover, drug release from tablets containing ternary mixtures of zein, co-excipients and 10% propranolol HCl was also studied. Results showed that zein matrices swelled rapidly at first, but then a plateau was reached, resulting in an initial rapid drug burst followed by slow drug release. HPMC tablets swelled to a greater extent and more gradually, providing a more constant drug release rate. EC did not practically swell, giving a nearly constant drug release pattern. Among the additives studied, only MCC increased the swelling of zein up to nearly three-fold, and thus suppressed drug burst from zein matrices and provided a nearly constant drug release over the test duration. Overall, the incorporation of co-excipients influenced the swelling behavior of zein to a greater extent compared to that of HPMC and EC, indicating that the molecular interactions of zein and additives are clearly more complex and distinct.